1992
DOI: 10.1007/bf00007671
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of cadmium, lead, copper and zinc inChironomus gr.thummi larvae (Diptera, Chironomidae) with deformedversus normal menta

Abstract: The concentrations of Cd, Pb, Cu and Zn in Chironomus gr. thummi were determined for 4th instar larvae from the polluted Dyle River, tributary of the Scheldt River (Belgium). Comparison was made between larvae with deformed and normal menta. Deformed larvae showed higher overall metal concentrations than normal larvae. Especially Pb and Cu had higher concentrations in deformed larvae (16.22 mg kgdry weight and 39.66 respectively) than in normal larvae (12.80 mg kg-1 dry weight and 35.70 respectively). No signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
3
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 20 publications
2
38
3
1
Order By: Relevance
“…Several studies have shown the relationship between the occurrence of structural deformities in Chironomidae larvae and degraded environmental conditions, resulting from contamination by heavy metals, herbicides, fungicides, and insecticides (Dermott, 1991;Warwick, 1985). According to Janssens De Bisthoven et al (1992), these deformities can be interpreted as a sign of sublethal pollutant concentrations which in the Imboassica Lagoon would probably be related to domestic sewage release and even to heavy metal presence. Deformities have been used in environmental impact evaluation studies on freshwater ecosystems (Janssens De Bisthoven et al, 1998;Diggins & Stewart, 1998), and suggested as a biological parameter to be included in long-term water-quality monitoring programs (Callisto et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the relationship between the occurrence of structural deformities in Chironomidae larvae and degraded environmental conditions, resulting from contamination by heavy metals, herbicides, fungicides, and insecticides (Dermott, 1991;Warwick, 1985). According to Janssens De Bisthoven et al (1992), these deformities can be interpreted as a sign of sublethal pollutant concentrations which in the Imboassica Lagoon would probably be related to domestic sewage release and even to heavy metal presence. Deformities have been used in environmental impact evaluation studies on freshwater ecosystems (Janssens De Bisthoven et al, 1998;Diggins & Stewart, 1998), and suggested as a biological parameter to be included in long-term water-quality monitoring programs (Callisto et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This group has been used as a bio-monitoring model for eco-toxicological tests (Warwick 1988;Jannssen de Bisthoven et al 1992) and has been included in both the Extended Biotic Index (De Pauw et al 1992) and the Annex V.1.2.6 of the E. C. Water Framework Directive. The larval stage is the stage of the Chironomids' life cycle when they are exposed to water and sediment contaminants.…”
Section: Chironomids (Diptera) a Group Important For Assessing Contamentioning
confidence: 99%
“…Since chironomids are still present in rivers heavily polluted with metals (Clements et al ., 1988 ;Janssens de Bisthoven et al, 1992), it is apparent that they are able to tolerate pollution . Yet, observations on increased metal tolerance in chironomids have shown contradictory trends.…”
Section: Introductionmentioning
confidence: 99%